Relationship between Intellectual Capital with Profitability and Productivity in Indonesian Banking Industry - Khairiyansyah Khairiyansyah; Vebtasvili Vebtasvili (Jurnal Keuangan dan Perbankan, 2018)
This study aims to examine the impact of Intellectual Capital (VACA, VAHU, STVA) on profitability and productivity. The population in this study is a Banking Company listed on the Indonesia Stock Exchange from 2014 to 2016. Samples obtained by a purposive sampling method obtained 30 banking companies from 2014 to 2016. It is an empirical study using PLS for the data analysis. The analysis using outer test models and the inner model. Research results show that Intellectual Capital has a positive impact on profitability (ROA). The higher the value of VAIC (Value Added Intellectual Capital), the higher the profitability of the banking company. This indicates that the company is getting better in managing the assets that result in an increased return on assets owned companies measured by ROA. Intellectual Capital has a positive impact on productivity (ATO), yet VAHU and STVA have no positive and significant effect on productivity, whereas VACA has a positive and significant influence on productivity. Companies have been able to use the physical capital to improve the efficiency of the company.JEL Classification: O34; D23DOI: https://doi.org/10.26905/jkdp.v22i1.1577